2-methoxybenzylidenepyruvate with heavier trivalent lanthanides and yttrium(III) - Synthesis and characterization - Ionashiro, E. Y. [UNESP]; Bannach, Gilbert [UNESP]; Siqueira, A. B. [UNESP]; de Carvalho, C. T.; Rodrigues, E. C.; Ionashiro, Massao [UNESP] (Springer, 2008)
Solid-state Ln(2-MeO-BP) compounds, where Ln stands for trivalent Eu to Lu and Y(III) and 2-MeO-BP (which is 2-methoxybenzylidenepyruvate) have been synthesized. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), X-ray powder diffraction, infrared spectroscopy and other methods of analysis were used to characterize and to study these compounds. on the base of the obtained results an Ln(2MeO-BP)(3)center dot H2O general formula can be established.
Keywords: characterization; heavier lanthanides; yttrium; 2-methoxybenzylidenepyruvate; thermal behaviour